IMPLEMENTASI KEBIJAKAN PEMELIHARAAN KENDARAAN DINAS OPERASIONAL PADA BIRO UMUM SEKRETARIAT DAERAH PROVINSI JAWA BARAT - , Dede Jaelani; , Kurhayadi; Deden Hadi Kushendar, (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of writing this article is to find out how far the Implementation of the Operational Service Vehicle Maintenance Policy at the General Bureau of the Regional Secretariat of West Java Province. The research method uses a qualitative approach. The problem is the implementation of official vehicle maintenance policies, operations are not optimal. The results of the discussion show that the implementation of public policies is influenced by several factors, including: organizational structure, resources, communication, and dispositions. Meanwhile, the implementation of the policy needs to be carried out in a comprehensive manner, which includes maintenance of vehicles and their SOPs. Inadequate human resources where there are no experts in asset valuation for the implementation of official vehicle maintenance policies. In carrying out innovations and breakthroughs in service to employees, discretion can be exercised in the implementation of public policies as long as they do not conflict with applicable norms and regulations.